Bifunctional flexible fabrics with excellent Joule heating and electromagnetic interference shielding performance based on copper sulfide/glass fiber composites. Issue 44 (3rd November 2021) - Liu, Binguo; Zhang, Qi; Huang, Yuanhui; Liu, Dong; Pan, Wei; Mu, Yunchao; Cheng, Xiaozhe; Qin, Yajie
Abstract : The flexible and wearable CuS/glass fiber-based nanocomposite fabricated via facile one-step surface modification of bare GFs followed by chemical deposition of CuS strategy. The proposed CuS/GFs displays excellent Joule heating and EMI shielding performance. Abstract : Flexible and wearable electronic technology is in great demand with the rise of smart electronic systems. Among these, multifunctional systems with high performance at low cost have attracted extensive attention of scholars from the practical application perspective. However, the fabrication of devices with multifunctionality without sacrificing their connatural flexibility advantages remains a huge challenge. In this study, a CuS-modified glass fiber first acts as a bifunctional wearable electronic device for superior thermal management and electromagnetic interference (EMI) shielding. Specifically, the inherent glass fiber was initially modified with a silane coupling agent for the amino group (–NH2 ) functionalization followed by further CuS deposition via a facile electroless plating technology. Interestingly, due to the strong interaction between CuS and the glass fiber through the coordinate –NH2 and Cu 2+, the prepared copper sulfide/glass fibers (CuS/GFs) not only keep the inherent flexibility and lightness of the fiber substrate, but also have excellent electrothermal conversion performance accompanied by a wide temperature range (38 °C–209 °C), low working voltage (0.3 V–1.5 V), and rapid response time (reaching 209 °C within 10 s at 1.5 V). Moreover, the prepared CuS/GF textile also exhibits interesting electromagnetic interference shielding efficiency (EMI SE) of 61 dB as well as a high specific shielding effectiveness up to 6130.65 dB cm 2 g −1 with a CuS mass loading of 9.95 mg cm −2 . These features confirm the potential of CuS/GFs as a flexible, wearable, and efficient electrical heater and EMI shielding material for the new type of intelligent electronic devices.